The Effect of Gender, Age and Tenure on Satisfaction Towards Co-Workers Among Academics in Malaysian Public Universities - Khairunneezam Mohd Noor; Siti Suriani Othman; Muhamad Zaki Mustafa; Safiyyah Ahmad Sabri; Kalsom Ali (Universiti Sains Islam Malaysia, 2024)
An understanding of job satisfaction, is a prerequisite to an integrative explanation of workers behavior at the workplace. This article analyses academics in higher education institutions satisfaction on co-workers and its differences based on demographic backgrounds. Using a simple random sampling technique, the researchers drew a sample of 1078 academics from three participating public universities. The findings indicated that the level of satisfaction with co-workers among academics was at the moderate level and there are differences of satisfaction based on demographic differences. The implications of the findings on co-workers satisfaction among academics in higher education institutions are discussed.